2016
DOI: 10.2105/ajph.2016.303181
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Feedback and the Viral Spread of Social Media Messages About Autism Spectrum Disorders

Abstract: Objective. To determine whether exchanges of emotional language between health advocacy organizations and social media users predict the spread of posts about autism spectrum disorders (ASDs). Methods. I created a Facebook application that tracked views of ASD advocacy organizations' posts between July 19, 2011, and December 18, 2012. I evaluated the association between exchanges of emotional language and viral views of posts, controlling for additional characteristics of posts, the organizations that produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 28 publications
0
35
0
3
Order By: Relevance
“…With fear-based approaches too comes the possibility of unintended effects such as dissonance or desensitization, as alluded to by Cho and Salmon [47]. However, a recent work from Bail [48] found that positive emotional content increased the virility of messages used for a social media Facebook campaign. Bail [48] suggests that social media campaigns must not rely on fear-based tactics to draw attention to their cause, but that campaigns may benefit from the use of positive emotional language.…”
Section: Investigating the Impact Of Employing Different Message Frammentioning
confidence: 99%
“…With fear-based approaches too comes the possibility of unintended effects such as dissonance or desensitization, as alluded to by Cho and Salmon [47]. However, a recent work from Bail [48] found that positive emotional content increased the virility of messages used for a social media Facebook campaign. Bail [48] suggests that social media campaigns must not rely on fear-based tactics to draw attention to their cause, but that campaigns may benefit from the use of positive emotional language.…”
Section: Investigating the Impact Of Employing Different Message Frammentioning
confidence: 99%
“…This cannot be countered merely by recitation of fact. Public health campaigns, especially on social media, need to invite emotional dialogue to be more successful, acknowledging and respecting the real fears of an audience who have doubts about the ability of the medical profession to help them [Bail, 2016]. Advocates for childhood vaccination need to employ greater pathos in their communication -simply stating 'these are the scientific facts.…”
Section: Discussionmentioning
confidence: 99%
“…Somewhere in the last 200 years it appears that feelings and emotions have been downplayed, or at worst ignored, victims of the general rationalisation and bureaucratisation of western society during that period [Weber, 1978]. To gain any traction in addressing vaccine hesitancy, government health agencies need to acknowledge the role of emotion in creating effective communication strategies [Bail, 2016].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations